Preparation and Self‐Assembly of a 2:1 Polyoxometalate‐Fullerene C60 Shape Amphiphile. Issue 38 (25th September 2018) - Zhou, Shengju; Wang, Lin; Yuan, Zaiwu; Chen, Mengjun; Zhang, Geping; Li, Hongguang
Abstract : An organic‐inorganic hybrid (5 ) is synthesized where two Dawson polyoxometalate (POM) moieties are linked to one fullerene C60 unit. In a POM‐friendly solvent such as DMSO, DMF and CH3 CN, 5 forms small vesicles below 100 nm at a concentration of 37.3 mg mL –1 . When the concentration decreases to 9.0 mg mL –1, detection of aggregates becomes difficult. However, supramolecular structures with diverse morphologies can be induced upon the addition of H2 O or toluene. In DMSO/H2 O and DMF/H2 O systems, plates form, which break to debris and small vesicles at high volume percentage of H2 O. In CH3 CN/H2 O mixtures, solid spheres form, which fail to further evolve into other self‐assembled structures. In DMSO‐based binary mixtures, the type of poor solvent has a big influence on the aggregation behavior of5, and replacing H2 O with toluene transfers the aggregates from plates to multilamellar and multicellular vesicles. In contrast, in CH3 CN‐based systems, the influence of the type of poor solvent is quite limited. Although the morphologies of the aggregates change a lot, their magnetic properties remain unchanged as confirmed by electron spin‐resonance measurements. Abstract : A unique amphiphile was prepared whereby two Dawson polyoxometalates were covalently connected to one fullerene C60 sphere. The amphiphile shows tunable aggregation behaviour in single and binary solvent mixtures controlled by collective effects of π–π interaction, electrostatic interaction and solvophobic effect. Two‐dimensional plates, solid spheres and vesicles have been observed, which represent a new class of multifunctional materials.